Islam - Jin, Yijiu; Chan, Alex Ching-shing; Ho, Wai-Yip (Religious studies in contemporary China collection, 2017)
Acknowledgements; Introduction; Section 1; Chapter 1 The Localization and Nationalization of Islam in China; Chapter 2 Architectural Styles of Mosques in China: Analysis and Comments; Chapter 3 Islamic Culture in Tibet; Chapter 4 A Brief Narrative of Chinese Style Islamic Relics; Chapter 5 Studies of Islam in China in the Twentieth Century; Section 2; Chapter 6 A Primary Investigation of the History of the Hui People and the Historical Data of Islam Recorded in the Notes Written by Zhou Mi; Chapter 7 Satuq Bughra Khan and the Beginning of Islamization in the Tian Shan Region